Study of Laterite Iron Ore Extraction by Smelting Method using Electric Arc Furnace - Wijayanti, Luluk Nofitasari; Choirunnisa, Aura Shafa; Azizi, Matrix Faqih (Journal of Metallurgical Engineering and Processing Technology, 2025)
Laterite iron ore resources have enormous potential. Laterite iron ore is the main material for iron and steel production in Indonesia, with reserves estimated at 1,391 million MT and Fe content between 40% and 56%. The processing and extraction of laterite iron ore carried out in this study used the Electric Arc Furnace (EAF) method. The processing process includes the stages of drying, crushing, mixing (two-stage mixing), sintering, reheating, and smelting. In the sintering and smelting processes, BCI semi coke is used as a reductant and energy source. While lime is used to help bind impurity minerals into slag. The selection of the EAF method is based on its advantages in energy efficiency and the ability to use more diverse raw materials. EAF can also produce high-quality products and has better environmental control than technologies such as blast furnaces. The variation in the composition of BCI semi coke and lime used in this experiment affects the final Fe content in the pig iron produced. The right process and using the appropriate material composition, pig iron with high Fe content can be obtained. The highest Fe content in the research conducted was 94.43%.